2019
DOI: 10.5664/jcsm.7768
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea, Sleepiness, and Glycemic Control in Type 2 Diabetes

Abstract: Study Objectives: Self-reported sleepiness is common in patients with obstructive sleep apnea (OSA) and is being increasingly recognized as an effect modifier of the association between OSA and cardiovascular outcomes. However, data on whether sleepiness modifies the association between OSA and glycemic outcomes are lacking. The current study sought to characterize the association between glycemic control and sleepiness in people with OSA and type 2 diabetes. Methods: Adults with non-insulin requiring type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Some studies show that OSA is associated with an increased risk of death and cardiovascular disease [ 2 , 3 ]. Type 2 diabetes is a frequent comorbidity in patients with OSA [ 4 6 ]. Intermittent hypoxaemia and sleep fragmentation in OSA could contribute independently to the development of insulin resistance, glucose intolerance and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that OSA is associated with an increased risk of death and cardiovascular disease [ 2 , 3 ]. Type 2 diabetes is a frequent comorbidity in patients with OSA [ 4 6 ]. Intermittent hypoxaemia and sleep fragmentation in OSA could contribute independently to the development of insulin resistance, glucose intolerance and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a few studies have shown that OSA severity as measured by hypoxemic burden during sleep is associated with insulin resistance and type 2 diabetes only in sleepy subjects (19,20). The issue of sex differences is also of interest; a previous study in patients with type 2 diabetes revealed that the relationship between OSA severity and HbA 1c was not seen in women (21), yet the current study suggested benefits of CPAP in women only.…”
mentioning
confidence: 56%
“…Moreover, several other blood metabolites other than 2 h-PG, HbA1c and uric acid, such as circulating complement component 3, CRP and erythropoietin, have recently been raised as promising biomarkers supporting the diagnosis of OSA [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%